1985
DOI: 10.3109/00365598509180267
|View full text |Cite
|
Sign up to set email alerts
|

Motility of the Human Ureter, with Special Reference to the Effect of Indomethacin

Abstract: Ureteral motility was studied in isolated preparations obtained from 19 patients at surgery. Contraction was monitored in an organ bath and contraction recorded isometrically. In all but one patient rhythmic activity with a frequency of 2.0 +/- 0.3 contractions/min was recorded. In 6 patients contractions had to be elicited by stimulation with prostaglandin E2 or F2 alpha. In the remaining cases motility started spontaneously within 30 min. In patients with bilharzia nephropathy various pathological types of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…sodium salicylate and aspirin which also inhibit prostaglandin synthe- sis. In agreement with our finding, in previous studies indomcthacin inhibited ureteral motil ity in vitro [25,26]. In our experiments, we added Bk into the bathing medium after the ef fect of prostaglandin synthesis blockers reach ed a steady level.…”
Section: Discussionsupporting
confidence: 92%
“…sodium salicylate and aspirin which also inhibit prostaglandin synthe- sis. In agreement with our finding, in previous studies indomcthacin inhibited ureteral motil ity in vitro [25,26]. In our experiments, we added Bk into the bathing medium after the ef fect of prostaglandin synthesis blockers reach ed a steady level.…”
Section: Discussionsupporting
confidence: 92%
“…Many in vitro physiological and pharmacological stud ies of the ureter [10,11] have shown an absence of sponta neous contractile activity. The present study shows that the ability of in vitro ureteral segments to generate sponta neous contractions depends on the method of cutting the ureter.…”
Section: Discussionmentioning
confidence: 99%
“…As reference we had to rely on sheep gallbladder strips which apparently qualita tively responded to cholinergic stimulation like human specimens. The selection of ovine gallbladders was a com promise since these specimens are always readily avail able from freshly slaughtered sheep and we have previous extense experience with smooth muscle preparations from sheep [9] which basically responded in a similar way to human specimens [10]. In our study we chose carbachol as a stimulant of contractility since we found that the nat urally occurring agonist cholecystokinin in a series of 12 experiments only resulted in a 59% efficacy (maximal response) as compared to carbachol (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the inhibition of ERA occurred after a certain latency period since prostaglandin inhibition requires some time and the bathing fluid was not changed upon administration, therefore probably some stimulating activity still remained in the bath. Large amplitude rhythmic contractions have previously been reported in a small number of cases with cholecystitis [12] and the cyclooxygenase inhibitor indomethacin has suc cessfully been used clinically in the treatment of acute bil iary pain [ 13], We previously described a similar situation in the human ureter where spontaneous large amplitude motility is governed by prostaglandins, and increased Gallbladder Motility Digestion 1997:58:368-372 rhythmic contractions were detected in ureteral irritation and ureteral disease [10].…”
Section: Discussionmentioning
confidence: 99%